Workshop Manajemen Pembelajaran Berbasis Digital di SMP Negeri 1 Amfoang Tengah - Desty A. Bekuliu; Yusuf Elpontus Tanaem; Nimrot Doke Para; Martin Ch. Liufeto; Nelci Non; Yampi R. Kaesmetan; Delfince Toleu; Endang Oekolos; Yafet Balan (I-Com: Indonesian Community Journal, 2023)
Community service activities are wrapped in the form of workshops based on digital learning and evaluation which is utilizing applications connected to the internet network. The purpose of this Community Service Activity (CSA) is to provide training and enhance teachers' understanding of learning management, specifically digital-based learning evaluation, at Junior High School (JSC) 1 Amfoang Center. The activity spans 2 days, involving 3 speakers who deliver materials and training to 14 teachers. The CSA implementation method includes presenting content on learning management, digital-based learning management, and digital-based learning evaluation. It also includes practical exercises in digital-based learning evaluation using the Slido platform, a website that facilitates interactive online discussions. The outcome of this workshop indicates that teachers gain knowledge and skills in conducting digital-based evaluations for mid-term exams and final semester exams using the Slido application.